Ibârat Is?t?ilâh?îyah; Suatu Kajian Tarjamah - Baiq Tuhfatul Unsi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2013)
Ibârat Is?t?ilâh?îyah (idiom) is a language units (can be a word, phrase, or sentence) whose meaning can not be